The Effect of Guided Inquiry Learning Model Based On Lesson Study For Learning Community On Chemical Equality Materials - Defista, Chesa; Andromeda, Andromeda; sopia, Eka (UIN Fatmawati Sukarno Bengkulu, 2022)
The learning process on chemical equilibrium material at Public Senior High School 1 Padang tends to use a teacher-centered learning model. This resulted in students' critical thinking skills did not develop because students were not actively involved in the learning process so it had an impact on student learning outcomes. Thus, the guided inquiry learning model can be one solution so that students can be actively involved. To maximize the implementation of the guided inquiry learning syntax, a learning system is applied, namely lesson study for the learning community. In lesson study-based learning for the learning community, learning will be planned and reflected on an ongoing basis. This study was conducted to determine the effect of the guided inquiry learning model based on lesson study for learning community on chemical equilibrium material on student learning outcomes at PUBLIC SENIOR HIGH SCHOOL 1 Padang. The research method is a quasi-experimental research with one group pretest-posttest design. Based on hypothesis testing with the Mann-Whitney test at a significance level of 5% (α = 0.05), the value of asymp sig. is <0.001. Then the value of asymp sig. (<0.001) <α (0.05), it can be concluded that the guided inquiry learning model based on lesson study for learning community on chemical equilibrium material affects student learning outcomes.